Antifungal effect in vitro of Origanum Vulgare in Candida Albicans strains - Villavicencio Gastelú, Jorge Eleodoro (2016)
Objective: To evaluate the in vitro antimycotic effect of Origanum vulgare essential oil on Candida albi-cans strain ATCC 10231 Material and method: Selection of four different oregano geotypes was carried out, the essential oils were obtained by distillation by Drag with steam; Its quantitative chemical com-position was determined by Gas Chromatography, Mass Spectrometry (GC / MS). The antimicrotic activity of essential oils was evaluated in vitro through sensitivity tests with the disk diffusion method in agar culture against C. albicans. Results: The results showed high antimycotic activity of all oils from the concentration of 12.5%. Conclusions: Essential oils of Origanum vulgare from different geotypes show differences in their antifungal effects. The essential oil of Origanum vulgare may be is a pharmacological alternative for the treatment of fungal infections in the mouth.